Data Configuration and Publication Trends for the Korean National Health Insurance and Health Insurance Review & Assessment Database - Hae Kyung Kim; Sun Ok Song; Junghyun Noh; In-Kyung Jeong; Byung-Wan Lee (Diabetes & Metabolism Journal, 2020)
Background Big data reports related to diseases and health care for the Korean population have been published since the National Health Insurance Service (NHIS) and the Health Insurance Review & Assessment (HIRA) Service provided limited open access to their databases. Here, we reviewed the structure, content, and means of using data from the National Health Insurance (NHI) system for the benefit of Korean researchers and presented the latest publication trends in Korean healthcare data procured from the NHI and HIRA databases. Methods Since 2013, researchers have been able to obtain nationwide population-based studies using the NHI and HIRA databases of the insured. We searched publications using the NHI and the HIRA databases between 2013 and 2019 retrieved from PubMed. Results The NHI and HIRA databases provide nationwide population-based data. The total number of publications from 2014 to 2019 using NHI and HIRA databases is 2,541 and 655, respectively. A total of 5,465 endocrinology-related studies were performed during 2014 to 2019. Conclusion The NHIS and HIRA databases have provided tools for guidelines to approach world-leading population-based epidemiology and disease research.